MULTIPEL SKLEROSIS TUMEFAKTIF - Dwi Astiny,* Reza Aditya Arpandy,* Riwanti Estiasari* (Neurona Majalah Kedokteran Neuro Sains, 2016)
MULTIPLE SCLEROSIS MS IS A RARE VARIANT OF MS IT REFERS TO DEMYELINATING BRAIN LESIONS MORE THAN 2CM IN WHITE MATTER REGION WITH MASSLIKE EFFECT OR VASOGENIC EDEMA AND POSTGADOLINIUM MAGNETIC RESONANCE IMAGING MRI TYPICALLY SHOWING AN INCOMPLETE RING ENHANCEMENT MRI OFFERS BY FAR THE MOST SENSITIVE TECHNIQUE FOR DETECTING MS LESION AND HAS PROVED TO BE AN IMPORTANT PARACLINICAL TOOL FOR DIAGNOSING MS